Highly Efficient Synergistic Chemotherapy and Magnetic Resonance Imaging for Targeted Ovarian Cancer Therapy Using Hyaluronic Acid‐Coated Coordination Polymer Nanoparticles - Guang Li; Shengying Shi; Jingxiu Tan; Lijuan He; Qiwen Liu; Feng Fang; Huijiao Fu; Min Zhong; Ziyi Mai; Rui Sun; Kun Liu; Zhenzhen Feng; et al. (Advanced Science)
Abstract The diagnosis and treatment of ovarian cancer (OC) are still a grand challenge, more than 70% of patients are diagnosed at an advanced stage with a dismal prognosis. Magnetic resonance imaging (MRI) has shown superior results to other examinations in preoperative assessment, while cisplatin‐based chemotherapy is the first‐line treatment for OC. However, few previous studies have brought together the two rapidly expanding fields. Here a technique is presented using cisplatin prodrug (Pt‐COOH), Fe3+, and natural polyphenols (Gossypol) to construct the nanoparticles (HA@PFG NPs) that have a stable structure, controllable drug release behavior, and high drug loading capacity. The acidic pH values in tumor sites facilitate the release of Fe3+, Pt‐COOH, and Gossypol from HA@PFG NPs. Pt‐COOH with GSH consumption and cisplatin‐based chemotherapy plus Gossypol with pro‐apoptotic effects displays a synergistic effect for killing tumor cells. Furthermore, the release of Fe3+ at the tumor sites promotes ferroptosis and enables MRI imaging of OC. In the patient‐derived tumor xenograft (PDX) model, HA@PFG NPs alleviate the tumor activity. RNA sequencing analysis reveals that HA@PFG NPs ameliorate OC symptoms mainly through IL‐6 signal pathways. This work combines MRI imaging with cisplatin‐based chemotherapy, which holds great promise for OC diagnosis and synergistic therapy.